Pengaruh Budaya Organisasi, Human Relation dan Job Description terhadap Etos Kerja Karyawan pada PT Asianagro Agung Jaya Tanjung Balai - Ari Rahman Zen; Normansyah Normansyah (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study addresses the issue of suboptimal employee work ethic in a labor-intensive palm oil processing company, where organizational factors are assumed to play a critical role. The purpose of this research is to examine the effect of organizational culture, human relations, and job description on employee work ethic at PT Asianagro Agung Jaya Tanjungbalai. A quantitative approach was applied using a saturated sampling technique involving 35 employees. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The findings reveal that organizational culture, human relations, and job description simultaneously have a significant effect on employee work ethic. Partially, each variable also shows a positive and significant influence. Among the independent variables, job description has the strongest contribution to improving work ethic. The coefficient of determination indicates that 39.6% of the variation in work ethic can be explained by the three variables, while the remaining is influenced by other factors outside this study. These results highlight the importance of strengthening internal organizational aspects to improve employee work ethic.